Visual search training in occupational therapy – an example of expert practice in community-based stroke rehabilitation. (November 2015) - Turton, Ailie J; Angilley, Jayne; Chapman, Marie; Daniel, Anna; Longley, Verity; Clatworthy, Philip; Gilchrist, Iain D
Introduction: Visual searching is an essential component of many everyday activities. Search training is practised as part of occupational therapy to improve performance skills both in people with hemianopia and those with spatial inattention post stroke. Evaluation of the effectiveness of such training first requires a systematic and detailed description of the intervention. To this end, this study describes the practice of a specialist occupational therapist. Method: Single sessions of intervention delivered by the occupational therapist to five participants with visual search disorders post stroke were video recorded. The recordings were analysed for content using a framework approach. Results: The occupational therapist educated participants about the impact of their visual impairment on everyday activities. She used instructions, spatial cueing, placement of objects and verbal feedback to train increased amplitudes of eye and head movements, to direct attention into the blind field or neglected space and to encourage systematic searching during occupations and activities. Activities were graded by manipulating the area for attention and complexity in the environment. Conclusion: This investigation provides a detailed description of a specialist occupational therapist's community-based intervention for improving visual search post stroke.